The gestural repertoire of Bwindi mountain gorillas (Gorilla beringei beringei): gesture form and frequency of use - Charlotte Grund; Martha M. Robbins; Catherine Hobaiter (Animal Cognition)
Abstract Over recent decades comprehensive catalogues of vocal, facial, and gestural signals have been established for most great ape species; however, a systematic description of wild gorilla gestural behaviour, particularly of the Eastern gorilla species, remains missing. We address this absence by cataloguing the physical form of gestural units used by 49 habituated wild mountain gorillas (Gorilla beringei beringei) from four social units in the Bwindi Impenetrable National Park, Uganda (n = 157 observation days over 8 months). We obtained a dataset of n = 3220 instances of intentional gesture, coded with a systematic ELAN-based framework (GesturalOrigins). Mountain gorillas employed a repertoire of 63 gesture actions, including potentially species-specific units, across 10 behavioural contexts. A latent class analysis on variants of gesture action expression split units further into 126 finer-grained forms (‘morphs’). We observed ~ 6 gestures per hour of observation time and species-level repertoire size was similar to those reported in both Pan species. Our study constitutes the first systematic description of the mountain gorilla gestural repertoire, providing a new understanding of their communication, filling current gaps in great ape gestural phylogeny, and complementing previous studies on their vocal signals. Living in cohesive, small-sized female-male bonded social units, gorillas show striking differences in social organisation as compared to Pan species and provide crucial context for theories on the potential ancestral states of human communicative behaviour.